Filsafat Behaviorisme Dalam PAUD Perspektif Rudolf Steiner - Zahratur Rahma; Maemonah Maemonah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
This article aims to understand the philosophy of Behaviorism in early childhood education from the perspective of Waldorf (Rudolf Steiner) which is applied to its usefulness in the learning process. Steiner is an educational theory commonly referred to as Waldorf, the word "Waldorf" usually alternates with the term Steiner. Describing schools with a curriculum based on Steiner's teachings is about humans who have ties associated with unraveling the mysteries of the spiritual world. At school Waldorf developed a model to develop creativity in the educational process. Waldorf has a kindergarten that differs from other schools in general. Waldorf educates kindergartens from 3-7 years old. Having a school curriculum that contains games that can hone children's development, such as games that discuss, fairy tales, fables, folklore, these games can increase motor skills and arts. According to the theory of behaviorism the results of learning experiences are the most changes in behavior. The interaction between stimulus and response occurs because of the learning process. The theory of learning behaviorism itself is interpreted to study human behavior, and there are three feelings regarding early childhood education supported by Waldorf teachers: respect, enthusiasm, and protection. a. Respect, enthusiasm and protection, b. Provide a responsive environment, c. Children's relationships with sensory experiences, d. in collaboration with peers, e. Learning by doing, f. Self responsibility and regulation.